Rantai Nilai Kopi dari Sistem Agroforestri di Jawa Barat: Menyeimbangkan Konservasi dan Komersialisasi - Widada, Arif Wahyu; Nasir, Muh Amat; Anggraini, Anila Indrianti (Lampung University, 2024)
Agroforestry, as an agroecological practice that integrates various production components in one system, has become an important approach in organic coffee cultivation in West Java, Indonesia. This study aims to_identify, analyse, and provide a financial assessment of the organic coffee value chain in agroforestry systems in the region. Using a mixed-methods approach, the study involved a survey of 60 agroforestry-implementing organic coffee farmers, in-depth interviews with local market players, and focus group discussions in Bandung and Sumedang districts. Data collection was conducted through purposive sampling for farmers, and snowball sampling for market actors. The results show that in agroforestry systems, farmers integrate coffee with other cash crops, with planting patterns changing from annuals to perennials over time. Smallholders have consistent knowledge of the coffee market, but show high interest in joining cooperatives. Coffee traders with varying scales of business, dominate farm-level sales. Few farmers sell directly to cooperatives or BUMDes. These findings provide important insights into the dynamics of organic coffee value chains in agroforestry systems in West Java, which can inform policy development to improve the economic and ecological sustainability of coffee agroforestry systems. Key words: value chain, coffee, household farmers